Indigenous vision : peoples of India, attitudes to the environment - Sen, Geeti (New Delhi : Sage Publications : India International Centre, 1992)
Contributed articles with reference to selected tribes.
Includes bibliographical references.
jakir
Keywords: Environmental protection -- India; Environmental policy -- India